Shape Memory Micro- and Nanowire Libraries for the High-Throughput Investigation of Scaling Effects - Oellers, Tobias; König, Dennis; Kostka, Aleksander; Xie, Shenqie; Brugger, Jürgen; Ludwig, Alfred (ACS combinatorial science, 2017)
The scaling behavior of Ti-Ni-Cu shape memory thin-film micro- and nanowires of different geometry is investigated with respect to its influence on the martensitic transformation properties. Two processes for the high-throughput fabrication of Ti-Ni-Cu micro- to nanoscale thin film wire libraries and the subsequent investigation of the transformation properties are reported. The libraries are fabricated with compositional and geometrical (wire width) variations to investigate the influence of these parameters on the transformation properties. Interesting behaviors were observed: Phase transformation temperatures change in the range from 1 to 72 °C (austenite finish, (A ), 13 to 66 °C (martensite start, M ) and the thermal hysteresis from -3.5 to 20 K. It is shown that a vanishing hysteresis can be achieved for special combinations of sample geometry and composition.